A decade of the international journal of lean six sigma: bibliometric overview. Issue 2 (1st July 2021) - Prakash, Surya; Kumar, Satish; Soni, Gunjan; Mahto, Raj V.; Pandey, Nitesh
Abstract : Purpose: This study aims to present an overview of leading research trends in the lean six sigma domain published in the International Journal of Lean Six Sigma ( IJLSS) since its inception. Design/methodology/approach: The study analyses articles published between 2010 and 2019 in IJLSS using the bibliometric technique. The results of data analysis identify the most prolific authors, their affiliation, citation trends and highly cited articles from the journal. Further, a graphical analysis involving bibliographic coupling and co-citation analysis of the corpus enriches the investigation. Findings: The results of the bibliometric analysis suggest that the number of IJLSS's publications and citations grew markedly over time (from 4 citations in 2010 to nearly 1, 324 in 2019). The organizational diversity and collaboration among authors publishing in IJLSS are trending upwards. Case study and focus group are the two most common research designs in publications. In the study, three major themes emerged: implementation of lean on business, integration of lean and six sigma and the effects of lean six sigma on businesses. Practical implications: The study finding informs and educates practitioners and scholars about various qualitative research tools, applications and methods of implementing lean six sigma tools in different industry sectors. Originality/value: The study uses bibliometric analysis to propose a novel categorization of research published in IJLSS and to report on the utilization of various lean tools in the journal. The study provides guidance for new future research besides offering a thorough introspection of the lean and six sigma domains.